Polscy emigranci wobec referendum w sprawie niepodległości Szkocji - Gąsior-Niemiec, Anna (Polityka i Społeczeństwo, 2021)
The paper focuses on the involvement of Polish migrants in the Scottish Independence Referendum of 2014. Based on the available evidence, it argues that political apathy and the alienation of migrants in their receiving countries should not be taken for granted. Exemplified by the active stance of the “Scottish” Poles, the paper demonstrates that the migrant groups’ political participation may depend on a country-specific nexus of factors to do with discursive construction of both their economic interests and civic belonging.